Pengaruh Kompensasi, Kompetensi, dan Pelatihan Karyawan terhadap Kinerja Karyawan CV. Tunas Makmur - Fitri Febriana; Diah Isnaini Asiati; Yunita Febriani (MOTIVASI, 2026)
Purpose– This study aims to determine and analyze the influence of compensation, competence, and training of employees of CV. Tunas Makmur, Ogan Komering Ilir Regency, simultaneously and partially. Design/methodology– This research uses an associative research method, with the variables being compensation, competency, and employee training. The population comprised 101 employees. A sample of 81 respondents was drawn using cluster sampling. The primary data used was collected using a questionnaire. Findings - The results of multiple linear regression testing indicate that simultaneously compensation, competence, and employee training have a positive and significant effect on employee performance at CV. Tunas Makmur, Ogan Komering Ilir Regency. Partially, it shows that compensation significantly affects employee performance, competence significantly affects employee performance, and employee training significantly affects employee performance at CV. Tunas Makmur, Ogan Komering Ilir Regency. The results of the coefficient of determination indicate that the variables of motivation, leadership, and work environment are able to contribute to the rise and fall of employee performance by 66%.